2014
DOI: 10.2196/jmir.2934
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Internet as a Health Information Resource Among French Young Adults: Results From a Nationally Representative Survey

Abstract: BackgroundThe Internet is one of the main resources of health information especially for young adults, but website content is not always trustworthy or validated. Little is known about this specific population and the importance of online health searches for use and impact. It is fundamental to assess behaviors and attitudes of young people looking for online health-related information and their level of trust in such information.ObjectiveThe objective is to describe the characteristics of Internet users aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
245
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(280 citation statements)
references
References 41 publications
22
245
1
12
Order By: Relevance
“…[5][6][7] However, adequate use of these resources depends on an individual's skill in finding and applying the information. 8 These skills have been conceptualized as health literacy (HL).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, adequate use of these resources depends on an individual's skill in finding and applying the information. 8 These skills have been conceptualized as health literacy (HL).…”
Section: Introductionmentioning
confidence: 99%
“…The second available and used method in this study was internet. In a study conducted Among French Young Adults, it has been found that The Internet is a useful tool to spread health information and prevention campaigns, especially to target young adults [6]. Also Jay and John [7] found that the Internet is starting to revolutionize health education research and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Percheski & Hargittai (2011) found that among college students, young adults with a higher education level (cultural capital) sought health professionals, friends and family more often than those with a lower educational attainment. Beck et al (2014) also found that manual labour status and income (economic capital) were negatively associated with seeking health information online and through health professionals. HISB is likely to be associated with the breadth and quality of one's social network (social capital), the financial means to access health care professionals and physical means of transportation (Savoleinen, 1995, Ackerson & Viswanath, 2009.…”
Section: Introductionmentioning
confidence: 92%